Kebijakan Pemberian Bantuan Sosial Bagi Keluarga Prasejahtera : Studi Kasus Di Gampong Meunasah Asan Kecamatan Blang Mangat Kota Lhokseumawe - Amru Alba; Rudi Kurniawan; Taufik Gunawan; Muhaddis Muhaddis (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
Pre-prosperous families do not understand that social assistance must be accounted for according to technical instructions. Recipients of social assistance do not know that the assistance they receive must be used according to the budget plan and the activity implementer must submit a report to the Directorate of Social Security, Ministry of Social Affairs of the Republic of Indonesia and BPKP to check whether the assistance is appropriate and on target. The aim of implementing this service is to provide understanding to underprivileged families that social assistance is provided selectively and recipients are researched professionally. Social assistance is provided to improve the standard of living of underprivileged families, paying attention to justice, propriety, rationality and benefiting from the principles of transparency, accountability, fairness and selectiveness. Social Assistance is assistance in the form of money or goods given to protect underprivileged families from social risks. The method used is socialization through seminars, problems are answered by collecting data, documentation and interviews. Partners in implementing this socialization are the village head, Village Representative Council, village figures and students. Researchers obtained data from underprivileged families regarding aid that was right on target, aid was not distributed all at once but was divided into stages and the use of the budget was checked by the Financial and Development Audit Agency.